Foresight older adults' quality of life in the aging crisis in Iran: A systematic review and meta-analysis - Raheleh Alimoradzadeh; Katayoun Jahangiri; Roya Alimoradzadeh (Experimental Gerontology)
Introduction: To provide foresight for the older adults' quality of life (QOL) in the aging crisis in Iran, this systematic review and meta-analysis study is conducted. Methods: All relevant articles were searched in the English and Persian databases such as Scopus, Web of Science, PubMed, Google Scholar, SID, and Medex regardless of the time range up to December 2023. Results: Out of 348 articles found, 8 articles were included finally. In total, the QOL of 1093 older adults' people with a mean age of 71.55 ± 6.91 years were evaluated. The study showed that the overall average of the QOL of the older adults is 58.5 ± 10.1 The overall average QOL of the older adults at the Iranian community level was 57.6 ± 15.5. The overall average QOL of the older adults in nursing homes are 60.1 ± 29.7. Conclusion: The Iranian older adults have an average QOL and paying attention to the older adults and their needs and designing interventions to improve their health status should be on the agenda of health policymakers.